Fixed-point-free embeddings of graphs in their complements - Seymour Schuster (International Journal of Mathematics and Mathematical Sciences)
The following is proved: If G is a labeled (p,p−2) graph where p≥2, then there exists an isomorphic embedding ϕ of G in its complement G¯ such that ϕ has no fixed vertices. The extension to (p,p−1) graphs is also considered.